Identification and Diagnosis of a Photovoltaic Module Based on Outdoor Measurements - Spagnuolo, G.; Lappalainen, K.; Valkealahti, S.; Manganiello, P. (2019 IEEE Milan PowerTech, 2019)
Photovoltaic modules may be subject to significant ageing during their lifetime. This is evident especially through the value of the series resistance, which is one of the five parameters appearing in the single diode model of the module. The identification of the series resistance value drift on the basis of on-field measurements is not trivial, because of the measurement noise and limitations in reaching the open circuit voltage conditions. In this paper, an approach to the identification of the operating parameters of the module through outdoor measurements is proposed. The method shows interesting features in view of its application to detecting module ageing phenomena during its lifetime.